What influences youth to operate all-terrain vehicles safely? - Grummon, A. H. (Oxford University Press, 2014)
The operation of all-terrain vehicles (ATVs) by youth has contributed to the incidence of serious and fatal injuries among children. This study explored factors related to the frequency with which youth wore a helmet and refrained from engaging in three risky driving behaviors (driving at risky speeds, on paved roads and on unfamiliar terrain) while operating an ATV. Youth (n = 248) aged 9–14 from central Ohio and one of their parents completed self-report measures of ATV safety behaviors, youth general propensity for risk taking, protection motivation and parental behaviors to facilitate youth safety. Data from two focus groups provided insight on quantitative results. Analyses revealed considerable variation in the frequency with which youth performed the safety behaviors, with 13- and 14-year-olds reporting less frequent safe behavior than 9- to 12-year-olds. Multiple regression analyses suggested that parental behaviors, such as providing reminders to wear a helmet, were associated with more frequent helmet use but were not associated with risky driving behaviors. Youth’s general propensity toward risk taking was not associated with helmet use and only associated with riskydriving behaviors among the 13- and 14-year-olds. Self-efficacy was an important predictor across both age groups and behaviors. Implications for injury prevention are discussed.